1974
DOI: 10.1111/j.1476-5381.1974.tb09651.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification by Drugs of the Secretagogue Effect of Dopamine on the Pancreas

Abstract: IThe specific stimulating action of dopamine and L-DOPA on exocrine pancreatic secretion was further investigated in the isolated blood-perfused canine pancreas. 2 6-Hydroxydopamine (I100 ig, i.a.) stimulated the secretion but was far less potent than dopamine. Epinine (0.3-1mg. i.a.), a-methyldopamine (10-300 ,g, i.a.) and octopamine (10-300 pg, i.a.) were ineffective. secretion. 5 These observations suggest that L-DOPA is probably converted to dopamine to stimulate the exocrine pancreas, and that dopamine in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1978
1978
1992
1992

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…The physiological role of the pancreatic dopamine receptors has not been elucidated, while dopamine is known to be present in the canine pancreas in a concentration of about 140 ng/g wet weight of tissue (6). The endogenous pool of dopamine cannot be assumed to be associated with neural structures, since 1) methamphetamine, which exerts its dopaminergic effects through the release of dopamine from the dopaminergic neurons, such as is the case with amphetamine (26-28), did not trigger pancreatic secretion in the present study, and 2)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiological role of the pancreatic dopamine receptors has not been elucidated, while dopamine is known to be present in the canine pancreas in a concentration of about 140 ng/g wet weight of tissue (6). The endogenous pool of dopamine cannot be assumed to be associated with neural structures, since 1) methamphetamine, which exerts its dopaminergic effects through the release of dopamine from the dopaminergic neurons, such as is the case with amphetamine (26-28), did not trigger pancreatic secretion in the present study, and 2)…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto and collaborators demonstrated that exogenous dopamine increases the secretion of pancreatic juice, of which the components are similar to those induced by exogenous secretin (2), and that there are specific dopamine receptors related to the exocrine pancreatic secretion in dogs (3)(4)(5)(6). Thus, the dopamine receptor response can be easily quantified by measuring the increases in volume of the pancreatic juice.…”
mentioning
confidence: 96%
“…We suggested that there were specific receptors for the secretion of the pancreatic juice by dopamine and that dopamine may play a physiological role in the secretory mechanism of the dog pancreas. Furthermore, infusion of secretin increased the dopamine content in the pancreatic tissues (8). This observation suggested that dopamine plays a role in secretin-stimulated secretion.…”
mentioning
confidence: 69%
“…Accordingly, the receptor mechanism for the rate of flow could not be clarified. However, it is apparent that the stimulatory effects of DA on the exocrine pancreas in rats are weak as opposed to the strong secretin-like effects in dogs (7,(10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 97%